If x y ( x + y ) = 1 , find the value of x 3 y 3 1 − x 3 − y 3 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
How do you manipulate?
Log in to reply
We first divide both sides by xy.
x y ( x + y ) = 1 ,
x + y = x y 1
Next we cube both sides:
x + y = x y 1 ,
( x + y ) 3 = ( x y ) 3 1
okay i understand
Problem Loading...
Note Loading...
Set Loading...
xy(x+y) = 1
If we manipulate this equation, we find that x 3 y 3 1 = ( x + y ) 3
Expanding the right side gives x 3 y 3 1 = x 3 + y 3 + 3 x y ( x + y )
Then we find
x 3 y 3 1 − x 3 − y 3 = 3 x y ( x + y )
And that 3 x y ( x + y ) = 3 × 1
Therefore the solution is 3.